Peningkatan Pengetahuan dan Ketrampilan Ibu Menyusui dengan Simulasi Modelling Digital Kontrasepsi Suntik di Klinik Permata Hati Karanganyar - Erna Wati; Deny Eka Widyastuti; Tresia Umarianti; Dheny Rohmatika (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
Breastfeeding is natural process that is not easy. The coverage of exclusive breastfeeding cannot be separated from the problems that occur in the breastfeeding process, including the wrong assumption that little milk comes out or breast milk not sufficient for the baby's needs. This condition is caused by several factors, including the food and drink consumed by the mother, psychological or emotional condition of the mother, and abnormal breast shape. A new method introduced to prevent and overcome this problem Digital Modeling Simulation of Injecting Contraception at the Permata Hati Clinic in Karanganyar. Purpose To find Injecting Contraceptive Digital Modeling Simulation at Permata Hati Clinic Karanganyar. The result of community service is that breastfeeding mothers at the Permata Hati Karanganyar clinic have increased the knowledge and skills of breastfeeding mothers with digital modeling simulations for injecting contraceptives at the Permata Hati Karanganyar Clinic. Increased knowledge 2 through digital modeling simulations, which initially was 13.6 increased to 15.6 and there was increased in breastfeeding. Based on the implementation of community service, it can concluded that there is an increase in the behavior of postpartum mothers in the use of contraceptives and the breastfeeding process.